Management of Juvenile Otosclerosis: A Systematic Review - Virginia Fancello; Luca Sacchetto; Chiara Bianchini; Andrea Ciorba; Daniele Monzani; Silvia Palma (MDPI AG, 2022)
Background. Otosclerosis can occur during childhood, resulting in the early onset of conductive hearing loss. The approach to a child with otosclerosis can present some difficulties in terms of diagnosis and treatment, and the literature on juvenile otosclerosis (JO) is still relatively limited. Aim. To explore the current approaches to JO, in order to clear the management of this condition and evaluate the outcomes and the possible complications of surgical treatment. Methods. A systematic review was performed according to PRISMA guidelines, searching Medline and Embase from January 2002 through to 30 September 2022. A total of 759 papers were identified but based on specified criteria, nine were included in this study. Results. There were 94 children affected by JO and treated by stapes surgery. According to the available data, Male: Female ratio was 1:3-4, whilst the mean ages ranged from 10 to 16.3 years at the time of stapes surgery. After stapes surgery, the target of ABG < 10 dB was achieved in most of the patients. Overall, the 4 complications were reported (4/94= 4%): stenosis of the external ear canal, deterioration of hearing, anacusis with vertigo, tinnitus. Conclusions. The heterogeneity of the available studies does not allow us to draw straight conclusions on this topic, currently. More data about the natural history of the disease in children could help in approaching the treatment correctly, and possibly in drawing guidelines. Studies with a prolonged follow-up could be helpful for assisting clinicians and families in taking the most favorable decision about treatment.